Case Report: Synovial chondromatosis in sport climbers fingers - Becker, Helmut; Iruretagoiena-Urbieta, Xeber; Schöffl, Volker (Frontiers in Sports and Active Living, 2025)
Introduction: Sport Climbing is a rapidly developing sport with an increasing variety and number of injuries, especially now that it is an Olympic event. The objective of this study is to firstly report the presence of Finger Synovial Chondromatosis (FSC) found in the fingers of climbers. Synovial chondromatosis is a rare condition and particularly rare in the hands and fingers. Methods: We prospectively evaluated all climbers with finger injuries presenting in 2022 for the presence of FSC in the finger joints. 13 patients in this case series were included with complaints of finger pain for more than 6 weeks. The study was performed in our Sports Medical Centre in Bamberg, Germany. The diagnosis was made based on in person clinical assessment, ultrasound examination and additional radiological findings (e.g., x-ray, CT, MRI) as applicable. Results: We detected 13 male climbers with FSC with experience ranging from intermediate to elite level. 77% (10/13) of the patients did not complain of any symptoms of the FSC and presented with other diagnoses (e.g.pulley rupture, tenosynovitis) and the finding of FSC was just an additional finding. In 12 subjects FSC was found in the proximal interphalangeal (PIP) joint and one in the metacarpo-pahalangeal (MCP) joint and distributed as follows: right (R) side 69%, left (L) side 38%, considering 15% in both hands. The prevalence corresponded to the digits are as follows: D2 15%, D3 77%, and D4 15%. Discussion: With the rapid development in sport climbing there has been a rise in the intensity, volume and variety of training, which may be the key factors contributing to the spectrum of injuries associated with climbing. Hand and finger climbing related injuries are well documented, however the incidental discovery of this rare condition warrants its inclusion as another differential diagnosis in the spectrum of climbing related pathologies. At the moment, not enough is understood about FSC and its long-term consequences therefore further analysis is warranted for future studies.
CRIS-Team Scopus Importer:2025-03-28
Keywords: chondromatosis; climbing; finger; finger injury; rock climbing